Emotional burnout health workers during the COVID-19 pandemic - Керимбаева, Рысты; Жамирова, Улмекен; Абдрахманова, Айгүл (Pedagogy and Psychology, 2020)
Article about the state of experiencing the syndrome of «emotional burnout» in the non-standard mode of work of medical workers in the COVID-19 pandemic. The issue of the impact of many negative factors on the professional activity of doctors, in connection with the Declaration of an emergency situation in Kazakhstan, an outbreak of coronavirus infection, is being considered. In the treatment of coronavirus infection, external and internal psychological causes of burnout syndrome in medical workers were identified. It is characterized by manifestations of emotional burnout, which are manifested in professional communication with feelings of fatigue, emotions, weakness, indifference, and anxiety. The issues of reducing the psychological state of medical workers in the conditions of coronavirus, their stress resistance, high anxiety, emotional will, features of self-control and management were considered. In the context of a pandemic, it is proposed to provide psychological assistance to medical workers, and state support for their work is recommended.